Predicting voluntary forage intake in cattle - C.A. Bandyk; R.C. Cochran (Kansas Agricultural Experiment Station Research Reports, 1998)
A large database was compiled of forage intake observations published during the past 20 years. Inputs included a wide range of factors believed to be related to voluntary intake. An analysis was designed to pinpoint which feed and animal characteristics were most valuable in predicting voluntary intake across a range of feeding situations and to compare the ability of different models to predict intake. Results emphasized the complexity of intake prediction. A wide range was evident in the variables included in the optimal models for predicting intake within different data subsets. In many cases, we observed that ratios between feed values (e.g., forage acid detergent fiber:forage crude protein) were more useful in predicting intake than the measures themselves.
Keywords: Kansas Agricultural Experiment Station contribution; no. 97-309-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 804; Cattlemen' s Day; 1998; Beef; Forage intake; Multiple regression; Prediction models